Embryogenesis and plant regeneration from isolated microspores of winter cauliflower (Brassica oleracea var. botrytis) - GU Hong-hui; TANG Gui-xiang; ZHANG Guo-qing; ZHOU Wei-jun (浙江大学学报. 农业与生命科学版)
The effects of various combinations of heat shock temperature and duration, medium renovation and cold shock pretreatment on the embryogenesis of isolated microspores were studied in two F1 hybrids of winter cauliflower (Brassica oleracea var. botrytis). The results indicated that the optimal combination of heat shock temperature and duration was 32℃ and 24 h. A decrease in sucrose concentration from 17% to 10% in liquid NLN medium following the first 24 h incubation at 32℃ significantly enhanced microspore embryogenesis. Both medium renovation and cold shock pretreatment markedly improved the quality of normal embryos and reduced the number of callus-like embryos. After 24 h induction at 32℃ and continuous culture at 24℃ in darkness for 30 d, isolated microspores produced normal embryos, which were then transferred to solid MS medium for embryo germination and root development. After two times of subculture, large amounts of normal regenerated plants were produced from generated shoots, and these regenerated plants were mainly spontaneous doubled haploids.